New species of Triplocania Roesler with forewing M3 forked (Psocodea: ’Psocoptera’: Ptiloneuridae), from Brazil - Da Silva Neto, Alberto Moreira; Rafael, José Albertino; Aldrete, Alfonso N. García (Zootaxa, 2014)
Four new Brazilian species of Triplocania with forewing M3 forked are described and illustrated based on male specimens, namely: Triplocania lamasi n.sp. (Mato Grosso: Brazil), Triplocania mariateresae n.sp. (Rio de Janeiro: Brazil), Triplocania newi n.sp. (Tocantins: Brazil) and Triplocania plaumanni n.sp. (Santa Catarina: Brasil). They differ from all the other species in the genus, in which the males are known, by the hypandrium and phallosome structures.